Museums in Building Social Capital - Panas, Nataliia; Панас, Наталія (Волинський національний університет імені Лесі Українки, 2020)
The article analyzes the role of museums in the formation of social capital in society, presents the possibilities of museum-type institutions in this context for Ukrainian society. The advantages of societies with a high level of social capital are highlighted; the urgency of this problem for our country is substantiated. Museums are a separate group of exceptional social institutions, the meaning of existence and the true nature of which was revealed and manifested only in the XXI century. Today, museums have gone far beyond their vision of decades past – in developed economies, they are becoming agents of social change, transforming social practices, helping to reduce antisocial phenomena and bringing significant benefits to local communities. We can compare how drastically the interpretation of the museum's mission and the vector of its activity in the era of globalization have changed in just some 20-30 years. Over the last decade, museums in Ukraine have responded more confidently to social and political problems in society, participated more actively in the consolidation of society, and generated new practices of cooperation with the local groups. The intensity of the media environ-ment, the rapid development of IT technologies help individual museums to more openly broadcast their communicative mission. At the present stage society is slowly but surely changing. Post-communist transformation, unpredictability of the political future, economic problems and military aggression in the east of the country have led to problems of adaptation of the population to new socio-economic conditions and test the resilience of our communities. All this changes everyday life and requires adaptation to new conditions. In this direction, provided a well-thought-out strategy and appropriate regula-tory framework, museums have significant positive potential.

У статті проаналізовано роль музеїв у формуванні соціального капіталу в суспільстві, представлено можливості закладів музейного типу в цьому контексті для українського суспільства. Висвітлено переваги суспільств із високим рівнем соціального капіталу, обґрунтовано актуальність цієї проблеми для нашої країни. Музеї – це окрема група виняткових соціальних інститутів, сенс існування та справжня природа яких вияви-лася й проявилася лише у XXI ст. Сьогодні музеї вийшли далеко за межі свого бачення минулих десятиліть – у розвинених економіках вони стають агентами соціальних змін, трансформуючи соціальну практику, допомагаючи зменшити асоціальні явища та приносячи значні прибутки місцевим громадам. Ми можемо порівняти, наскільки кардинально змінилась інтерпретація місії музею та вектор її діяльності в епоху глобалізації лише за якихось 20–30 років. Упродовж останнього десятиліття музеї в Україні більш упевненіше реагують на соціальні та політичні проблеми в суспільстві, беруть активнішу участь у консолідації суспільства, генерують нові практики співпраці з населенням. Інтенсивність медійного середовища, стрімкий розвиток ІТ-технологій допомагають окремим музеям усе активніше відкрито транслювати свою комунікативну місію. На сучасному етапі в українському суспільстві повільно, але таки відбуваються глобальні зміни. Посткомуністична трансформація, непрогнозованість політичного майбутнього, економічні проблеми та військова агресія на Сході країни призвели до проблем адаптації населення до нових соціально-економічних умов і перевіряють стійкість наших громад. Усе це змінює повсякденне життя й вимагає адаптації до нових умов. У цьому напрямі за умови добре продуманої стратегії та відповідного нормативного поля музеї мають суттєвий позитивний потенціал.
Музеї в справі побудови соціального капіталу
Keywords: social capital; museums; culture; economics; Ukraine; ransformation; development; соціальний капітал; музеї; культура; економіка; Україна; трансформація; розвиток; 316.7: 304